B-Annulated 1, 4-dihydropyridines as Notch inhibitors. Issue 20 (1st November 2018) - Gómez-Galeno, Jorge E.; Hurtado, Cecilia; Cheng, Jiongjia; Yardimci, Ceren; Mercola, Mark; Cashman, John R.
Graphical abstract: Highlights: Notch trafficking plays a role in many cancer processes. Evaluated b-annulated dihydropyridines in a Notch reporter assay. Identified chiral (+)-7 as a potent inhibitor of Notch trafficking. (+)-7 also inhibited proliferation in a colorectal cancer cell line (HCT-116) Abstract: The Notch signaling pathway is involved in cell proliferation and differentiation, and has been recognized as an active pathway in regenerating tissue and cancerous cells. Notch signaling inhibition is considered a viable approach to the treatment of a variety of conditions including colorectal cancer, pancreatic cancer, breast cancer and metastatic melanoma. The discovery that the b-annulated dihydropyridine FLI-06 (1) is an inhibitor of the Notch pathway with an EC50 ≈ 2.5 μM prompted us to screen a library of related analogs. After structure activity studies were conducted, racemic compound 7 was identified with an EC50 = 0.36 μM. Synthesis of individual enantiomers provided (+)-7 enantiomer with an EC50 = 0.13 μM, or about 20-fold the potency of 1.